Percepción de los efectos económico-financiero-social de los incentivos tributarios la exoneración del impuesto a la salida de divisas para las operaciones de financiamiento externo, y la reducción de 10 puntos porcentuales de la tarifa del impuesto a la renta sobre el monto reinvertido en la adquisición de maquinaria nueva, su aprovechamiento en el sector económico - industrias manufactureras (textiles, prendas de vestir y cuero) dentro del Distrito Metropolitano de Quito, periodo 2011 a 2013 - Cahuasquí Arroba, Verónica Nathalí (2014)
The Government through its company as responsible of the tax caudation, Internal Revenues Service, has created several tax incentives, with the purpose of promoting the achievement of its aims. Tax incentive are a benefit of the Government, and it can adopt diverse schemes of calculation, such as exonerations, exemptions, deductions, others; all this, in exchange to have the essential qualifications, those can be of social, economic or financial character, trying by this way, to strengthen the productive counterfoil and to stimulate the investment. On the other hand, the values that the Government stops perceiving by this concept, composes the referred Tributary Expense. The textile sector, is a former industry, its activities generate a high level of operations, in which one finds the intervention of the taxes of direct or indirect form.